1996
DOI: 10.1074/jbc.271.35.21200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Purinergic Receptor Channels and Their Role in Calcium Signaling and Hormone Release in Pituitary Gonadotrophs

Abstract: ] i oscillations by increasing the frequency, base line, and duration of Ca 2؉ spiking. In addition, ATP stimulated gonadotropin secretion and enhanced agonist-induced gonadotropin release. ATP was found to be secreted by pituitary cells during agonist stimulation and was promptly degraded by ectonucleotidase to adenosine. These observations indicate that ATP represents a paracrine/autocrine factor in the regulation of Ca 2؉ signaling and secretion in gonadotrophs, and that these actions are mediated by P 2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
85
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 58 publications
9
85
1
Order By: Relevance
“…Such basal ATP release was enhanced in cells simulated by ARL67156, an inhibitor of ectonucleotidases [13]. GnRH-induced stimulation of gonadotropin release was accompanied by elevation in basal ATP release, raising the possibility that ATP is stored in the secretory vesicles of these cells [2]. This is consistent with an earlier study showing calcium dependence of ATP release [23].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Such basal ATP release was enhanced in cells simulated by ARL67156, an inhibitor of ectonucleotidases [13]. GnRH-induced stimulation of gonadotropin release was accompanied by elevation in basal ATP release, raising the possibility that ATP is stored in the secretory vesicles of these cells [2]. This is consistent with an earlier study showing calcium dependence of ATP release [23].…”
Section: Discussionsupporting
confidence: 81%
“…Using the technique of single-cell calcium measurement, the initial characterization of purinoceptors in anterior pituitary cells were identified [2][3][4][5][6]. These experiments revealed that functional P2X receptors are operative in all secretory cell types.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations